Legal Protection For Victims Of Sexual Violence In Legal Abortion Services - Japono, Saskia Salsabila; Waluyo, Bambang (Dinasti Research, 2025)
This study aims to examine legal regulations that guarantee protection for victims of sexual violence in Indonesia, including the fulfillment of women's rights to obtain legal abortion services due to pregnancy resulting from sexual violence. The background of this study is based on the limited access of victims to safe abortion services despite being regulated in legislation. This study is important to assess the gap between legal norms and practices in the field in protecting victims. The method used is normative juridical with analysis of laws and regulations and other legal norms through literature study. The results of the study show that although Law Number 12 of 2022 concerning Sexual Violence Crimes, the Health Law, and the new Criminal Code have provided a legal basis for victims to access safe abortions, their implementation is still hampered by limited facilities, social stigma, and a lack of understanding among officials and medical personnel. In conclusion, it is necessary to strengthen the implementation of regulations and increase the understanding of stakeholders. The novelty of this research lies in its comprehensive analysis of the relationship between victim protection regulations and the implementation of legal abortion in Indonesia.